Obstacles to The Implementation of Chemical Castration for Perpetrators of Sexual Violence Against Children from A Medical Perspective - Jorza Sepmiko; Nur Husein Amrah; Lukman Hakim; Rahmat Saputra (KRTHA BHAYANGKARA, 2026)
This study analyzes the implementation of chemical castration as an additional punishment for child sexual abuse offenders in Indonesia (Law No. 17 of 2016) and its alignment with legal principles, utilitarian ethics, and medical ethics. Although intended as a deterrent and a means to prevent recidivism, empirical data indicate that sexual abuse rates have increased, and courts tend to avoid its application due to concerns over disproportionality and reduced rehabilitative potential. A normative-descriptive approach was employed, based on a literature review of laws and regulations, court decisions, academic journals, and related literature. Findings reveal that chemical castration imposes punishments disproportionate to the severity of the offense, fails to significantly reduce recidivism, and creates socio-economic burdens due to long-term side effects. Additionally, its implementation raises ethical conflicts for medical professionals, as the obligation to carry out court orders conflicts with the principles of non-maleficence and professional autonomy. The study concludes that chemical castration as an additional punishment is ineffective and introduces complex legal, social, and ethical challenges. Policy reevaluation, alternative restorative and rehabilitative measures, and harmonization between criminal law and medical ethics are recommended.